2016
DOI: 10.1007/s00228-016-2173-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of piperine on the pharmacokinetics of fexofenadine, a P-glycoprotein substrate, in healthy volunteers

Abstract: The results suggest that altered pharmacokinetics and enhanced bioavailability of FEX might be attributed to PIP-mediated inhibition of P-gp drug efflux. Therefore, intake of PIP or dietary supplements containing PIP may potentially enhance the absorption or bioavailability of P-gp substrate drugs in addition to FEX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…This was observed trough increased C max , AUC, T 1/2 and decreased K el and CL/F of chlozoxazone when administered with piperine. The same authors [179] found very similar effect of piperine intake to bioavailibility of fexofenadine, where piperine treatment significantly increased C max of fexofenadine and AUC time curve, as well as decreased CL/F of this drug. A 3-fold increase in C max and 1.5-fold increase in AUC were found for tetrahydrocannabinol, while a 4-fold increase in C max and a 2.2-fold increase in AUC were observed for cannabidiol when co-administered with piperine [159].…”
Section: Effect Of Piperine On Oral Bioavailability Of Drugs and Natumentioning
confidence: 71%
“…This was observed trough increased C max , AUC, T 1/2 and decreased K el and CL/F of chlozoxazone when administered with piperine. The same authors [179] found very similar effect of piperine intake to bioavailibility of fexofenadine, where piperine treatment significantly increased C max of fexofenadine and AUC time curve, as well as decreased CL/F of this drug. A 3-fold increase in C max and 1.5-fold increase in AUC were found for tetrahydrocannabinol, while a 4-fold increase in C max and a 2.2-fold increase in AUC were observed for cannabidiol when co-administered with piperine [159].…”
Section: Effect Of Piperine On Oral Bioavailability Of Drugs and Natumentioning
confidence: 71%
“…In Caco‐2 cells, the transport of digoxin and cyclosporine A, which is mediated by P‐gp, was inhibited by piperine with IC 50 values of 15.5 and 74.1 μM, respectively . Piperine was found to be associated with elevated maximum plasma concentration (C max ) and area under the curve (AUC) values of fexofenadine (a P‐gp substrate), thus decreasing the drug's total clearance . It was found to inhibit CYP3A enzyme mediated metabolism of triazolam to triazolam‐1′‐hydroxylation in a noncompetitive inhibition model .…”
Section: Introductionmentioning
confidence: 99%
“…The doses of PIP used in the rats were 5 and 10 mg/kg which were adopted from another study for adult rats ( Malini et al, 1999 ). The doses of PIP in the present study may be clinically relevant, since PIP in clinic trials has been tested for its potential to affect bioavailability of other compounds in food and dietary supplements and the dose of PIP used was 20 mg for humans ( Shoba et al, 1998 ; Bedada and Boga, 2017 ).…”
Section: Discussionmentioning
confidence: 99%